Pendampingan Masyarakat Dalam Rehabilitasi Hutan dengan Memanfaatkan Teknologi Geospasial di Desa Resapombo Kabupaten Blitar - Gea Aliajanah Gea; Alfi Sahrina; Putri Agustina Nur Baiti; Rini Retnosari; Izzati Farhatun Nisa (Jurnal Pemberdayaan Masyarakat, 2024)
Agriculture is a great potential in Resapombo Village. However, over time the community has not been able to use the land properly so that the land becomes less productive. The land experiences landslides, especially when rain occurs due to the absence of standing plants or trees that become water catchment. There is a need for forest rehabilitation by utilizing geospatial technology. Forest rehabilitation aims to restore forest functions. The methods used in this community service activity are coordination and socialization to the community, plant breeding, planting seedlings, aerial photography, and aerial photo processing, as well as making maps. The result of this community service activity is the Map of the Forest Rehabilitation Planting Area of Resapombo Village-Blitar Regency. The map made can be utilized in effective and efficient forest management and plant monitoring to be optimal. People with high enthusiasm and awareness and concern for the surrounding environment, especially forests, are provisions for the success of forest rehabilitation carried out. The community is expected to be more protective and understand the importance of forests for their survival, especially for the next generation.